Variability in the substitution pattern of hydroxypropyl cellulose affects its physico-chemical properties - Gilles Cremer; Sabine Danthine; Vera Van Hoed; Anne Dombree; Anne-Sophie Laveaux; Christian Damblon; Romdhane Karoui; Christophe Blecker (Heliyon, 2023)
Hydroxypropyl cellulose (HPC) is a water-soluble polymer with many applications in food, pharmaceutical, medical, or paints industries. Past studies have reported that differences in functionality can occur between products of similar pharmaceutical grades. Understanding the origin of these differences is a major challenge for the industry. In this work, the structure and physico-chemical properties of several HPC samples of the same commercial grade were studied. Structural analysis by NMR and enzymatic hydrolysis were performed to study molar substitution and distribution of substituents along the polymer chain respectively. Water-polymer interactions, surface properties as well as rheological and thermal behavior were characterized to tentatively correlate them with the structure, and gain new insights into the structure-function relationship of this polymer. The differences in structure revealed between the samples affect their properties. The unexpected behavior of one sample was attributed to a more heterogeneous substitution pattern, with the coexistence of highly and weakly substituted regions along the same polymer chain. The more block-like distribution of substituents has a great effect on the clouding behavior and surface tension reduction ability of the polymer.